Implementation Of Islamic Character Education in MI Ma'arif Blendangan During The Covid-19 Pandemic - Muhammad Rahmad Putra Purnama; Hanif Cahyo Adi Kistoro (Linguanusa : Social Humanities, Education and Linguistic, 2023)
Introduction to The Problem : The online learning regulations issued by the government make researchers worry about how educators implement Islamic character education online. Purpose : This study aims to find out what the values of Islamic character are, how to implement Islamic character education during the covid-19 pandemic, and the problems and solutions at MI Ma'arif Blendangan. Design/methods/approach: Qualitative research through a descriptive approach. Techniques for collecting data using interviews and documentation. Data analysis is carried out by summarizing the data, then presenting the data, then concluding. Findings : The results of the study, the values of Islamic character in MI Ma'arif Blendangan are religious, tolerant, honest, disciplined, polite, responsible, independent, creative, devoted to parents, likes to read. The implementation of Islamic character education at MI Ma'arif Blendangan is integrated into online learning and normal habituation for students at each home. Problems in implementing Islamic character education during the COVID-19 pandemic stem from internal student factors and external student factors. The solutions that educators do in overcoming problems are reminding habituation, providing quota assistance, providing relief from collecting assignments, providing prayer habituation forms, optimizing WhatsApp groups, and learning to use social media. Research implications/limitations: This research still has shortcomings and limitations, namely the type of research in more in-depth data analysis. Originality/value : Suggestions for further research to be more detailed in researching to get data or analysis that is more focused and in-depth.